REVIEW OF THE ACCURACY OF THE DIAGNOSIS CODE OF DENGUE HAEMORRHAGIC FEVER IN MEDICAL RECORDS IN RSUD dr. RASIDIN PADANG - Deni Maisa Putra; Yulia Fitriani; Dian Novita; Anadya Afriyanti; Washi Fadhila (Universitas Hang Tuah, 2023)
ABSTRACT The accuracy of the code is needed so that the information resulting from the diagnosis and action is accurate. However, the authors found that at RSUD dr.Rasidin Padang there were still incorrect codes. This is because the diagnosis of Dengue Haemorrhagic Fever is not correct in giving the code according to the ICD-10. The purpose of this study was to determine the accuracy of the diagnostic code for dengue haemorrhagic fever in medical records at dr.racidin. This research method used is quantitative with a descriptive approach. This research was conducted from February to May 2022. The number of samples was 59 medical records using the total sampling method, and the tool used was a checklist table with univariate analysis. The results of this study were obtained from 59 medical records, there were 37 (62.7%) medical records with inappropriate codes, and a small proportion of 10 (16.9%) medical records that were not clearly written, and there were 39 incomplete diagnosis writings. (66.1%) this was due to errors in determining the diagnosis code, doctors' writings that were difficult to read, incomplete completeness, non-specific written diagnoses based on ICD-10, and the use of abbreviations that were not standardized in hospitals. Therefore, researchers suggest that coders should pay attention to the rules and procedures for coding a diagnosis based on ICD-10. Keywords: Coding Accuracy, Clarity, Completeness